2006
DOI: 10.1128/jb.188.3.988-998.2006
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the Glucosyltransferase ( gtfBC ) Operon by CovR in Streptococcus mutans

Abstract: Streptococcus mutans is an important etiological agent of dental caries in humans. The extracellular polysaccharides synthesized by cell-associated glucosyltransferases (encoded by gtfBC) from sucrose have been recognized as one of the important virulence factors that promote cell aggregation and adherence to teeth, leading to dental plaque formation. In this study, we have characterized the effect of CovR, a global response regulator, on glucosyltransferase expression. Inactivation of covR in strain UA159 res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
156
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 87 publications
(166 citation statements)
references
References 69 publications
(99 reference statements)
3
156
0
1
Order By: Relevance
“…The overlap includes genes for cell-wall division and biofilm formation ( gbpB , lysM, gtfB , gtfC ), with VicR positively regulating these genes and CovR acting as a repressor [107,141,142]. In EMSA assays, it was observed that VicR Sm VicR and CovR co-bind the promoter regions of lysM , gbpB , and gtfC [107].…”
Section: Interactions Of Vicrk Tcs With Other Regulatory Systemsmentioning
confidence: 99%
See 3 more Smart Citations
“…The overlap includes genes for cell-wall division and biofilm formation ( gbpB , lysM, gtfB , gtfC ), with VicR positively regulating these genes and CovR acting as a repressor [107,141,142]. In EMSA assays, it was observed that VicR Sm VicR and CovR co-bind the promoter regions of lysM , gbpB , and gtfC [107].…”
Section: Interactions Of Vicrk Tcs With Other Regulatory Systemsmentioning
confidence: 99%
“…Later studies revealed that CovR Sm negatively or positively regulates about 6.5% of the S. mutans genome [142]. More importantly, CovR Sm directly represses a panel of genes required for the synthesis of water-soluble and water-insoluble glucan ( gtfB , gtfC ) and other exopolysaccharides derived or not from sucrose ( epsC and ftf ), as well as surface proteins GbpC and GbpB that bind to glucan [107,141,142]. Deletion of covR Sm reduced S. mutans cariogenicity in rat models by mechanisms not completely understood, but likely by affecting biofilm structure [162].…”
Section: Tcs Covrs and Covr As An Orphan Regulatormentioning
confidence: 99%
See 2 more Smart Citations
“…All the constructs were sequenced. For chromosomal expression of GFP or its derivatives, DNA fragments carrying gfp genes with the P 23 promoter were amplified from pIB184 derivatives and cloned into pIB107, a plasmid used for integration at the SMU.1405 locus (Biswas & Biswas, 2006). The resulting plasmids were linearized by BglI and transformed into S. mutans to obtain the desired strains.…”
Section: Construction Of Chromosomally Integrated Gfp Reporter Strainsmentioning
confidence: 99%